2020
DOI: 10.4102/sajce.v10i1.564
|View full text |Cite
|
Sign up to set email alerts
|

Questioning techniques used by Foundation Phase Education students teaching mathematical problem-solving

Abstract: The research question that guided this research study was the following: which questioning techniques do Foundation Phase Education students use when teaching mathematical problem-solving lessons? Background: Developing the questioning skills of Foundation Phase Education students when teaching mathematical problem-solving is often a neglected area of student curricula.Aim: This gap in mathematics programme is the focus of this study. Three main components were identified: presentation of mathematical problem-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Over the years, research has been conducted locally and internationally on different aspects of in-service FP teachers' experiences (Bruce 2011;Cekiso, Meyiwa & Mashige 2019;Kanjee & Mthembu 2015;Masnan, Sharif & Josin 2018;Meiring 2019;Sheldon 2015), on FP pre-service teachers' experiences during their teaching practice (Matzembacher, Gonzales & Do Nascimento 2019;Steyn & Adendorff 2020;Zinn et al 2014) and on the LS module in the FP at higher education Background: In South Africa socio-economic problems such as poor health conditions, juvenile delinquency, high rates of school dropout and teenage pregnancy are increasing. Therefore, it is vital to prepare foundation phase (FP) pre-service teachers to fortify children with basic life skills (LS) that will help them to cope with real-world challenges and demands.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, research has been conducted locally and internationally on different aspects of in-service FP teachers' experiences (Bruce 2011;Cekiso, Meyiwa & Mashige 2019;Kanjee & Mthembu 2015;Masnan, Sharif & Josin 2018;Meiring 2019;Sheldon 2015), on FP pre-service teachers' experiences during their teaching practice (Matzembacher, Gonzales & Do Nascimento 2019;Steyn & Adendorff 2020;Zinn et al 2014) and on the LS module in the FP at higher education Background: In South Africa socio-economic problems such as poor health conditions, juvenile delinquency, high rates of school dropout and teenage pregnancy are increasing. Therefore, it is vital to prepare foundation phase (FP) pre-service teachers to fortify children with basic life skills (LS) that will help them to cope with real-world challenges and demands.…”
Section: Introductionmentioning
confidence: 99%
“…Students still do not feel brave to ask questions or respond to questions from teachers or friends. Thus, the ability to ask questions in mathematical learning still needs to be a concern to be developed better (Bosch et al, 2018;Franke et al, 2009;Hendriana, 2017;Hendriana, Hidayat, & Ristiana, 2018;Hendriana, Rohaeti, & Hidayat, 2017;Lim et al, 2020;McCarthy et al, 2016;Steyn & Adendorff, 2020;Way, 2008).…”
Section: Leading the Discussionmentioning
confidence: 99%
“…His research found that learning in a synchronous online, face-to-face collaborative group study enables students to overcome problem-solving steps more systematically with the help of multiple ideas within group members. Steyn & Adendorff (2020), through their research stated that effective questioning practice for teaching mathematical problemsolving must be explicitly taught to foundation phase education students as part of the curriculum. All…”
Section: Introductionmentioning
confidence: 99%